Analysis of Road and Rail Transport Indicators for Containers from Seaports (Study Case: Lattakia Port) - الوادي محمد; رستم اكرم; زعتر نور (Latakia University Journal -Engineering Sciences Series, 2021)
The increase in shipping flows leads to dealing with large quantities of containers and thus congestion of sea ports, which affects the carrying capacity of the ports in addition to increasing costs and transport times commensurate with the increase in congestion. Road congestion also affects the efficiency and reliability of freight flows and thus on the prices of goods transported by switching from the road to other means of transportation can create a smooth transportation system to reduce road congestion. The use of the full potential of the railways will provide part of the solution to these problems. This research includes a description of the study area (lattakia port), studing the reality of the road and rail transport network, and collecting traffic data (truck fleet - waiting times - loading and unloading times). The available data showed that 99.9% of the total container transport traffic for the year 2019 by road transport, While the rate of rail transport does not exceed 0.1%.Further, the research also included counting trucks every hour for several days of different months of the year, and the analysis of the results showed that there is a change in the peak hours for the movement of trucks entering and leaving the seaport, accompanied by great waiting times